Kemampuan Pedagogical Content Knowledge (PCK)Mahasiswa Calon Guru Pendidikan Biologi Fkip Ums Dalam Menyusun Rpp Kurikulum Ktsp Tahun AJARAN 2015/2016 - Gumilar, REtno; , Dra. Hariyatmi, M.Si (2016)
This study was aimed to analysis of Content Knowledge (CK), Pedagogy Knowledge (PK) and Pedagogical Content Knowledge competence (PCK) pre-service teachers in preparing RPP. The experiment was conducted in November until Apryl 2016 at the Departement of Biology Education FKIP UMS. The study population was all pre-service teachers period 2012made lesson plan KTSP curriculum take a course PPL. Samples were taken by random sampling are 52 preservice teachers. The method used is descriptive qualitative method. Data collection was conducted of sheet identify research instrument CK, PK, and PCK competence on lesson plan document pre-service teachers. The results of data analysis showed that in general the ability CK of biology student teachers including good value with an average of 65%, ability PK teachers in general the result show a good value (71%), and ability PCK in general the results show a good value (62%).